Implementing Cooperative Learning Using Co-Op Co-Op Method to Enhance Studentsâ Ability to Determine Explicit and Implicit Information in Reading Comprehension - Yulantana, Theandin Kurnias; Rochsantiningsih, Dewi; *, Hersulastuti (Proceeding of International Conference on Teacher Training and Education, 2016)
Co-Op Co-Op is one of the cooperative learning strategies. It alllows students to work together in smallgroup to advance their understanding and provides them with the opportunity to share the understandingwith their peers. The research aims describing at (1) whether Co-Op Co-Op Method can improve studentsâreading comprehension in determining detail information and (2) the difficulties of using Co-Op Co-Opmethod to enhance the studentsâ reading comprehension especially in determining explicit and implicitinformation. This research applied a Classroom Action Researchand it was conducted in two cycles. Theresult of the research showed that (1) Co-Op Co-Op method can improve the studentsâ readingcomprehnsion in determining the detail information; explicit and implicit information. The means of thestudentsâ score improved from cycle to cycle. (2) There are some difficulties of using Co-Op Co-Opmethod in teaching reading comprehension to determine detail information; explicit and implicitinformation such as (a) implementing Co-Op Co-Op method takes long time because the students shoulddiscuss, present, provide the materials as well as doing the exercises (b) it is very difficult to control allgroups and hold them in group discussion because some of them still were passive (c) higher levelstudents usually take turn more than the lower one especially in the the discussing the materials andpresenting the materials.